2014
DOI: 10.1007/s10683-014-9393-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting cooperation in nonlinear social dilemmas through peer punishment

Abstract: Many social dilemmas exhibit nonlinearities and equilibrium outcomes in the interior of the choice space. This paper reports a laboratory experiment studying whether peer punishment promotes socially efficient behavior in such environments, which have been ignored in most experimental studies of peer punishment. It compares the effectiveness of peer punishment in a linear public good game to the effectiveness of this decentralized enforcement mechanism in two nonlinear social dilemma games: a piecewise linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…In this respect, using a common pool resource game, Ostrom, Walker, and Gardner () observe that peer punishment alone (i.e., without communication among group members) does not enhance cooperation. Moreover, Cason and Gangadharan () find that the impact of punishment is weaker and takes longer to effect in a nonlinear public good game and a common pool resource game than in a linear public good game. In these games the Nash equilibria and the socially efficient outcomes are less obvious than in a linear public good game, making it harder to identify free riding and cooperation (see Cason and Gangadharan , 69–72).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, using a common pool resource game, Ostrom, Walker, and Gardner () observe that peer punishment alone (i.e., without communication among group members) does not enhance cooperation. Moreover, Cason and Gangadharan () find that the impact of punishment is weaker and takes longer to effect in a nonlinear public good game and a common pool resource game than in a linear public good game. In these games the Nash equilibria and the socially efficient outcomes are less obvious than in a linear public good game, making it harder to identify free riding and cooperation (see Cason and Gangadharan , 69–72).…”
Section: Discussionmentioning
confidence: 99%
“…Although they do not provide individual data in their papers, their studies seemingly share the pulsing behavior. On the other hand, Cason and Gangadharan (2014) used an experimental design with n=4, where our theory predicts that the Nash equilibrium is unstable. However, the standard errors of the individual data are quite low, and they report that peer punishment works well.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was the first to use a nonlinear payoff function for a CPR experiment. Since the procedure for experiments with nonlinear payoff functions is complicated, many experimental social scientists still use linear payoff functions (Noussair et al 2011;Osés-Eraso and Viladrich-Grau 2011;Botelho et al 2014;Becchetti et al 2015), although some do use nonlinear functions 600 Tatsuyoshi Saijo et al (Rodriguez-Sickert et al 2008;Vyrastekova and Van Soest 2008;Hayo and Vollan 2012;Cason and Gangadharan 2014). Second, the number of appropriators is eight in their experiments, which is unusually high for CPR experiments.…”
Section: Example 1 (The Wgo Model)mentioning
confidence: 99%
See 1 more Smart Citation
“…Spraggon (, ) and Cason and Gangadharan (, ) reported results using a nonlinear revenue function, whereas other studies introduced nonlinearity in the cost function (Ostrom, Walker, & Gardner, ). Cason and Gangadharan () showed that nonlinearities could play an important role in the effectiveness of instruments for improving cooperation in social dilemmas, as in more complex nonlinear settings, the optimal choices become more difficult to identify. In this study, we choose the more realistic environment of a nonlinear payoff function, with a quadratic private revenue function.…”
mentioning
confidence: 99%